A protocol for the evaluation of the PneumoWave biosensor in supported accommodation settings: A study on feasibility and acceptability (RESCU-2) - Basak Tas; Lewis Beer; Elizabeth Appiah-Kusi; Will Lawn; Iona Belov; Polly Radcliffe; Andrew Radley; Bruce Henderson; Osian Meredith; Catriona Cowan; Stuart Kelly; Holly Maxwell Pringle; et al. (PLoS ONE, 2025)
Background People who overdose on opioids when they are alone or unmonitored are at heightened risk of death as other people do not know they should provide an emergency response. Wearable technology provides an opportunity to continuously measure respiratory function and ultimately send an alert if respiratory depression occurs. Objective This study evaluates the feasibility and acceptability of PneumoWave DC in UK homeless hostels or supported accommodation settings (equivalent to Housing First in the USA) for individuals at high risk of opioid overdose. The PneumoWave system consists of a wearable biosensor that is affixed to the chest and records chest motion and which, in future, could potentially provide early detection of respiratory depression and trigger overdose response. Methods RESCU-2 is a non-randomised, observational trial conducted in supported accommodation facilities across the UK. 50 participants who currently use opioids and live in homeless hostels in England and Scotland will wear the PneumoWave biosensor for varying periods to collect data over 2,000 participant-days. The biosensor will be linked via Bluetooth to a hub for continuous respiratory data collection. Self-reported drug use during the trial will be measured using drug diaries. Quantitative acceptability data will be measured using structured satisfaction surveys, while qualitative acceptability data will be obtained from interviews and focus groups with both residents and staff. Statistical analysis will include descriptive evaluation of feasibility outcomes, while qualitative data will undergo thematic analysis. The primary objectives of the study are: 1) feasibility of the study protocol within the hostel setting; 2) acceptability and usability of the device among people who use opioids and live in hostels; 3) acceptability of the device among staff who work in hostels and respond to overdose events. Primary outcomes are recruitment, total hours of usable data collected and successful recording of key outcome measures, among others. Trial registration: ISRCTN12060022. Results & Significance Findings will inform the feasibility of future integration of chest biosensor technology into hostel settings, assessing participant adherence, usability, and acceptability among people who use substances and staff. Insights gained will support the design of future trials and further development of remote monitoring technologies for overdose prevention and response strategies.